Analysis of Land Suitability for Arabica Coffee in Toba Regency, North Sumatra, Indonesia - Nora, Silvia; Mawardi, Surip; Kuswardani, Retna Astuti; Mawardi, Surip; Wijoyo, Hadi; Gandaseca, Seca; Novita, Aisar (International Journal of Biosciences and Biotechnology; Vol 11 No 1 (2023): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2023.v11.i01.p07, 2023)
Coffee is a mainstay plantation commodity in Toba Regency which is managed independently by the community where the land around the Lake Toba area is one of the potential lands in Toba Regency for developing Arabica coffee commodities because geographically Toba Regency is located at an altitude of 900 meters to 2,200 meters above sea level and directly borders Lake Toba. The strong roots of coffee plants make this plant one of the mainstays in preserving forests, restoring critical land, preventing erosion and flooding during the rainy season. The aim of this research is to analyze the land suitability of Arabica coffee plantations in Toba Regency. The method used to analyses the land suitability by using the matching method which was carried out by matching land characteristics with parameters/ criteria for plants based on Land Map Unit (LMU). The research results show that the area of Toba Regency based on the Geographic Information System (GIS) is 207,518.31 ha. Very suitable (S1) land suitability for Arabica Coffee Plants covering an area of 67,844.68 ha (32.69%), an area of 132,030.09 ha (63.62%) has S2 suitability class and an area of 7,643.54 ha (3.68%) has marginal suitability (S3). The potential land suitability class for coffee plants in Toba Regency becomes very suitable (S1) covering an area of 67,844.68 ha or 32.69%, moderate suitable class (S2) with temperature limitation covering an area of 132,030.09 ha (63.62%) and marginal suitability (S3 with temperature limitation) covering an area of 7,643.54 ha or 3.68%. Nutrient deficiencies were corrected by adding phosphorus (P) fertilizer of 4.19 kg P/ha or 9.31 kg SP36/ha or 11.63 kg TSP/ha. Nitrogen (N) fertilizer is 75 kg N/ha or the equivalent of 166,625 Kg Urea/ha. Potassium (K) fertilizer as much as 3 kg KCl/ha. Compost fertilizer is 10.56 tons of compost/ha.